Analysis of the impact of impeller outlet width on the steepness of pressure characteristic - Miltykh, Viktoriya; Sotnyk, Mykola (Eastern-European Journal of Enterprise Technologies, 2016)
The impeller outlet width is one of the most important geometrical parameters, which has a significant effect on the pressure characteristic of centrifugal pumps. The steepness of the pressure characteristic, in turn, determines selection of the pump control in the system. Finding a mathematical dependency between them will make it possible to design the impellers of centrifugal pumps with a predetermined steepness. To find the dependence between the impeller outlet width and the steepness of a pressure characteristic, we carried out numerical simulation. 30 double-entry impellers of centrifugal pumps with a specific speed from 80 to 210 with different values of the width of the impeller were simulated. Using numerical modeling data, we established dependences between the impeller outlet width b2 and the steepness of the pressure characteristic KH, and also consumable parameter qр, of the viewand . The coefficients a, k, E and F in the equations are variable and depend on the design features of Impeller. In order to use the established dependencies in the design of any double-entry impellers, it is necessary to determine the main geometric parameters of the impellers, which greatly influence the coefficients a, k, E and F.